2013
DOI: 10.1002/ejoc.201300878
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Multivalent Approach to α‐L‐Fucosidase Inhibition

Abstract: To probe the utility of a multivalent approach for fucosidase inhibition, a series of di‐ and tri‐valent imino sugars based on L‐fuco‐configured 1,4‐imino‐ and 1,4‐bis(imino)‐cyclitol epitopes has been synthesized and analyzed for fucosidase inhibition with the best trivalent species yielding a modest improvement in binding constant. Structural analysis of a representative pair of mono‐ and tri‐valent imino sugars has been performed on a bacterial fucosidase, BtFuc2970. The 3D structures show binding of the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 52 publications
(30 reference statements)
0
27
0
1
Order By: Relevance
“…A few years after the report of a strong multivalent effect in glycosidase inhibition, several studies investigating the mechanisms at play were reported by the groups of Compain, Gouin, Ortiz Mellet, Robina and others. [24,28,29,39] Different physical techniques and approaches were used; they included ITC, competitive lectin-enzyme experiments, AFM and X-ray. On the basis of studies reported in the field of carbohydrate-lectin interactions and by analogy with mechanisms operating in the case of proteins with single binding sites, [11,14,17] the multivalent effect in glycosidase inhibition can be explained in terms of several binding modes (Scheme 10).…”
Section: Understanding the Multivalent Effect In Glycosidase Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few years after the report of a strong multivalent effect in glycosidase inhibition, several studies investigating the mechanisms at play were reported by the groups of Compain, Gouin, Ortiz Mellet, Robina and others. [24,28,29,39] Different physical techniques and approaches were used; they included ITC, competitive lectin-enzyme experiments, AFM and X-ray. On the basis of studies reported in the field of carbohydrate-lectin interactions and by analogy with mechanisms operating in the case of proteins with single binding sites, [11,14,17] the multivalent effect in glycosidase inhibition can be explained in terms of several binding modes (Scheme 10).…”
Section: Understanding the Multivalent Effect In Glycosidase Inhibitionmentioning
confidence: 99%
“…In a study devoted to exploration of the impact of multivalency on a-l-fucosidase inhibition, Robina et al reported the first X-ray structure of a multivalent iminosugar-glycosidase complex. [39] Among the library of di-to trivalent systems evaluated with different aromatic scaffolds, multivalent effects were observed only with 28, which was found to be seven times more potent than the parent monovalent analogue 29 against a-lfucosidases from bovine kidney and Bacteroides thetaiotaomicron GH29 (BtFuc2970, Scheme 11). Crystal structures of…”
Section: Afm and Dls Experimentsmentioning
confidence: 99%
“…More recently, 14 and 15 ,23 16 ,24 and 17 25 (Figure 9) have been developed to interfere with biologically relevant carbohydrate‐processing enzymes, such as the glycosylceramide synthase and glucocerebrosidase involved in the metabolism of glycosphingolipids,23 the glycogen phosphorylase (GP) that catalyzes the breakup of glycogen into glucose‐1‐phosphate,24 and human α‐ L ‐fucosidase that is overexpressed or downregulated in several different pathologies including cancer, cystic fibrosis (CF), and fucosidosis 25. Multivalency was also explored against the β ‐ galactosidase from E. coli.…”
Section: Multivalent Carbohydrate‐mimics For Glycosidase Inhibition—fmentioning
confidence: 99%
“…a maximal concentration of 35 µM during inhibition assays). 27 The structure of 2a was confirmed by its T-symmetry deduced from the 13 C NMR spectrum recorded in DMSO-d 6 as well as by mass spectrometry.…”
Section: Scheme 3 Synthesis Of C-glycoside Cluster 2amentioning
confidence: 91%